Predictive factors of mortality in patients with pelvic fracture and shock submitted to extraperitoneal pelvic packing - FONSECA,VINICIUS CORDEIRO (2022)
ABSTRACT Introduction: in recent decades, the extraperitoneal pelvic packing technique has been disseminated, but there are still few studies. Thus, it was decided to analyze the results of extraperitoneal pelvic tamponade, in patients with pelvic fracture and shock, in order to identify predictive factors for mortality. Methods: a retrospective review of medical records of patients submitted to extraperitoneal pelvic packing was conduced. We analyzed their characteristics, prehospital and emergency room data, pelvic fracture classification, associated and severity injuries, laboratory and imaging exams, data on packing, arteriography, and other procedures performed, complications, hemodynamic parameters, and amount of transfused blood products before and after packing. Results: data were analyzed from 51 patients, who showed signs of shock from prehospital care, presence of acidosis, with high base deficit and arterial lactate levels. Most patients underwent multiple surgical procedures due to severe associated injuries. The incidence of coagulopathy was 70.58%, and overall mortality was 56.86%. The group of non-surviving patients presented significantly higher age, prehospital endotracheal intubation, and lower Glasgow Coma Scale scores (p<0.05). The same group presented, before and after extraperitoneal pelvic packing, significantly worse hemodynamic parameters of mean arterial pressure, pH, base deficit, hemoglobin, and arterial lactate (p<0.05). The non-surviving group received significantly more units of packed red blood cells, fresh frozen plasma and platelets within 24 hours following extraperitoneal pelvic packing (p<0.05). Conclusion: age and base deficit are independent predictors of mortality in patients submitted to extraperitoneal pelvic packing.